ITRAQ analysis of colorectal cancer cell lines suggests Drebrin (DBN1) is overexpressed during liver metastasis. Issue 11 (17th April 2014) - Lin, Qifeng; Tan, Hwee Tong; Lim, Teck Kwang; Khoo, Avery; Lim, Kiat Hon; Chung, Maxey C. M.
<x xml:space="preserve">Abstract</x> Colorectal cancer is currently the third in cancer incidence worldwide and the fourth most common cause of cancer deaths. Mortality in colorectal cancer is often ascribed to liver metastasis. In an effort to elucidate the proteins involved in colorectal cancer liver metastasis, we compared the proteome profiles of the human colon adenocarcinoma cell line HCT‐116 with its metastatic derivative E1, using the iTRAQ labelling technology, coupled to 2D‐LC and MALDI‐TOF/TOF MS. A total of 547 proteins were identified, of which 31 of them were differentially expressed in the E1 cell line. Among these proteins, the differential expressions of translationally controlled tumour protein 1, A‐kinase anchor protein 12 and Drebrin (DBN1) were validated using Western blot. In particular, DBN1, a protein not previously known to be involved in colorectal cancer metastasis, was found to be overexpressed in E1 as compared to HCT‐116 cells. The overexpression of DBN1 was further validated using immunohistochemistry on colorectal cancer tissue sections with matched lymph node and liver metastasis tissues. DBN1 is currently believed to be involved in actin cytoskeleton reorganisation and suppresses actin filament cross‐linking and bundling. Since actin reorganisation is an important process for tumour cell migration and invasion, DBN1 may have an important role during colorectal cancer metastasis.